Byzantine Battleships and Military Transport Vessels along the Hostile Shores - Hristov, Yanko; Kostadinova, Dafina (Studia Ceranea, 2021)
The establishment of the Bulgarian Khanate along the Lower Danube River and the Northern Black Sea coast changed the geo-political situation in the early medieval Southeastern Europe. It is beyond doubt that the Bulgarians did not develop navy or commercial fleets at that time. However, one cannot reveal substantial reserves about the statement that Khan Asparukh’ descendants were not completely disadvantaged by their Black Sea coastline that they managed to keep under control due to political and military reasons. This becomes clear if the prolonged series of clashes between Byzantium and Bulgaria in 750s–770s are taken into consideration. Despite an obvious usefulness of the cooperation between land armies and navy squadrons in those endeavors, as well as the nonchallenged Byzantine maritime supremacy along the Black Sea shores, the Imperial navy met substantial difficulties or did not completely accomplish its tasks on many occasions.